2024
DOI: 10.1002/hsr2.1816
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced healing of wounds that responded poorly to silver dressing by copper wound dressings: Prospective single arm treatment study

Oxana Gorel,
Mozna Hamuda,
Ilana Feldman
et al.

Abstract: Background and AimsDressings containing silver ions are an accepted and common option for wound treatment. However, some wounds fail to heal at the desired rate despite optimal management. The aim of the study was to examine the effect of copper dressings in noninfected wounds.MethodsThe study included 20 patients aged 18–85 years with 2–30 cm2 noninfected wounds treated for 17–41 days with silver wound dressings that failed to reduce by >50% the wound size, who were then treated with copper dressings. Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It was found that the use of bandages involving copper nanoparticles enhanced the healing of hard-to-heal wounds. At the same time, bandages with copper nanoparticles proved to be more efficient than dressings containing silver nanoparticles [39].…”
Section: Introductionmentioning
confidence: 97%
“…It was found that the use of bandages involving copper nanoparticles enhanced the healing of hard-to-heal wounds. At the same time, bandages with copper nanoparticles proved to be more efficient than dressings containing silver nanoparticles [39].…”
Section: Introductionmentioning
confidence: 97%